Time of Discharge and 30-Day Re-Presentation to an Acute Care Setting After Elective Lumbar Decompression Surgery. Issue 3 (16th March 2023) - Sastry, Rahul A.; Hagan, Matthew; Feler, Joshua; Abdulrazeq, Hael; Walek, Konrad; Sullivan, Patricia Z.; Abinader, Jose Fernandez; Camara, Joaquin Q.; Niu, Tianyi; Fridley, Jared S.; Oyelese, Adetokunbo A.; Sampath, Prakash; et al.
Abstract : BACKGROUND: Evidence regarding the consequence of efforts to increase patient throughput and decrease length of stay in the context of elective spine surgery is limited. OBJECTIVE: To evaluate whether early time of discharge results in increased rates of hospital readmission or return to emergency department for patients admitted after elective, posterior, lumbar decompression surgery. METHODS: We conducted a retrospective cohort study of 779 patients admitted to hospital after undergoing elective, posterior, lumbar decompression surgery. Multiple logistic regression evaluated the relationship between time of discharge and the primary outcome of return to acute care within 30 days, while controlling for sociodemographic, procedural, and discharge characteristics. RESULTS: In multiple logistic regression, time of discharge earlier in the day was not associated with increased odds of return to acute care within 30 days (odds ratio [OR] 1.18, 95% CI 0.92-1.52, P = .19). Weekend discharge (OR 1.99, 95% CI 1.04-3.79, P = .04) increased the likelihood of return to acute care. Surgeon experience (<1 year of attending practice, OR 0.43, 95% CI 0.19-1.00, P = .05 and 2-5 years of attending practice, OR 0.50, 95% CI 0.25-1.01, P = .054), weekend discharge (OR 0.49, 95% CI 0.27-0.89, P = .02), and physical therapy evaluation (OR 0.20, 95% CI 0.12-0.33, P < .001) decreased the likelihood of discharge before noon. CONCLUSION: Time of discharge is not associated with risk of readmission or presentation to the emergency department after elective lumbar decompression. Weekend discharge is independently associated with increased risk of readmission and decreased likelihood of prenoon discharge.